Passerini-type reaction of boronic acids enables α-hydroxyketones synthesis - Kai Yang (Nature Portfolio, 2021)
Multicomponent reactions enable the rapid construction of diverse molecular scaffolds with modularity and step economy. In this work, the authors report the use of boronic acids as carbon nucleophiles in a Passerini-type three-component coupling reaction towards an expanded inventory of α-hydroxyketones.